Pedigree Analysis of Warmblood Horses Participating in Competitions for Young Horses - Próchniak, Tomasz; Kasperek, Kornel; Knaga, Sebastian; Rozempolska-Rucińska, Iwona; Batkowska, Justyna; Drabik, Kamil; Ziȩba, Grzegorz (Frontiers in Genetics, 2021)
The aim of the study was to characterize the population structure and assess the genetic diversity of warmblood horses used in the show jumping discipline. Pedigree data of 1048 horses participating in the Polish Championships for Young Horses were analyzed. The pedigree of these animals included 12 863 individuals. The study consisted in analysis of the pedigree structure of the horses and characterization of the homozygosity and genetic diversity in the population. It was found that pedigree completeness and depth were sufficient for reliable assessment of the genetic diversity in the analyzed population. Although the average inbreeding coefficient exhibited at an acceptable level (approx. 1.01%), the increasing percentage of inbred animals seems disturbing. The results have shown that modern sport horses are derived from a small number of high-quality sires whose offspring were intensively used for breeding - bottleneck effect. In consequence, a greater part of the genetic variation reduction was observed in the non-founder generations. Given the changes in the studied population, the level of inbreeding in modern sport horses should be monitored, and pedigree data should be effectively used in selection for mating.